Aprendizaje-Servicio para el fortalecimiento de las habilidades blandas de séptimo grado de la Institución General Básica Alonso de Mercadillo, Loja 2023 - Armijos Chamba, Thalia Michelle (2023)
This research focuses on analyzing the relationship between service-learning and the strengthening of soft skills in seventh-grade students of the Institución General Básica Alonso de Mercadillo, Loja, during the 2022-2023 academic period. Although there is research on service-learning in other countries, no contextualized proposals have been made for this specific environment. The research poses questions to guide the search for and collection of information. The methodology used combines qualitative and quantitative approaches in a non-experimental design. Various tools have been used, such as document analysis, interviews, observation sheets and focus groups. The first phase collected quantitative data, laying the groundwork for the second phase, which was qualitative in nature. Scientific methods such as descriptive, deductive, analytical and statistical methods were used to approach the study of the variables in question and to obtain a complete and detailed view of the relationship between service-learning and the strengthening of soft skills in students. Keywords: service-learning and soft skills, role of the teacher, teaching-learning